Density and Ultrasonic Study of Benzothiazole and Chlorobenzothiazole at 298.15K. (2016) - Pund, Dinesh A.; Tayade, Dipak T.; Naik, Anil B.
Abstract: Ultrasonic refers to study of sound waves, which are higher frequency than the human audible range. It is widely used in many applications viz. medical, underwater, food and oil technology etc. The Intermolecular interaction plays an important role in the development of molecular science. Substituted benzothiazole plays a vital role in the biological field such as anti-allergic, anti- inflammatory analgesic, and fungicidal activity. Therefore, present work is carried out to study the substituted benzothiazole with different concentrations at 298.15K with 2 MHz. The acoustical parameters; adiabatic compressibility, linear free length, acoustic impedance, relative association etc evaluated with experimental values of density and ultrasonic velocity. It is observed that the density and ultrasonic velocity increases with increase the concentration of solute while adiabatic compressibility and linear free length deceases. The intermolecular interactions have been observed at molar concentrations, which suggest the solute-solvent interaction.